2021
DOI: 10.1186/s13027-021-00401-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to evaluate outcomes in long-COVID-19 and post-COVID survivors

Abstract: SARS-CoV-2 infection can impact the physical, cognitive, mental health of patients, especially in those recovered in intensive care units. Moreover, it was proved that the effects of the virus may persist for weeks or months. The term long-COVID or post-COVID syndrome is commonly used for indicating a variety of physical and psychological symptoms that continue after the resolution of the acute phase. This narrative review is aimed at providing an updated overview of the impact of physical, cognitive, and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 90 publications
0
16
0
3
Order By: Relevance
“…Long-term health consequences of COVID-19 remain unknown, but reports suggest that prolonged symptom duration and limitations in functioning are common among hospitalised as well as non-hospitalised adults [13,14] and children [15,16]. The spectrum of longlasting symptoms is wide and varies from mild discomfort to severe adverse effects on physical, cognitive, and psychosocial health [17], with important wider implications on functioning, including employment and school attendance.…”
Section: Post-covid Condition Health Consequencesmentioning
confidence: 99%
“…Long-term health consequences of COVID-19 remain unknown, but reports suggest that prolonged symptom duration and limitations in functioning are common among hospitalised as well as non-hospitalised adults [13,14] and children [15,16]. The spectrum of longlasting symptoms is wide and varies from mild discomfort to severe adverse effects on physical, cognitive, and psychosocial health [17], with important wider implications on functioning, including employment and school attendance.…”
Section: Post-covid Condition Health Consequencesmentioning
confidence: 99%
“…In addition to the high risk of SARS-CoV-2 infection for healthcare professionals, it has been seen that they have experienced several mental problems, such as anxiety, stress, and burnout syndrome, a further problem to the already complicated working conditions in the pandemic phase. This could suggest the design of ad hoc programs for the prevention of mental disorders alongside health surveillance [ 29 , 30 , 31 , 32 , 33 ]. In support of this, it was shown that work overload and stress represented risk factors in contracting infectious diseases; in particular, this risk increased as the number of working hours increased, exposing HCWs for a longer time to patients, viruses, and mental stress [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the acute phase, patients affected by COVID-19 infection may also experience a systemic disease that lasts for four or more weeks following the acute phase of infection. This condition, known as Long COVID, may present severe fatigue, breathlessness, neurocognitive deficits, headaches, joint pain, and a decline in the quality of life [57][58][59]. This clinical picture may be due to different factors, related to both hospitalization, such as post-intensive care syndrome (PICS) or social isolation, associated with the specific COVID-19 infection, and to the infection itself, such as residual inflammation or viral organ damage [58].…”
Section: Covid-19mentioning
confidence: 99%
“…In this setting, neurocognitive impairment represents one of the most important factors affecting recovery, with patients experiencing difficulties in attention, concentration, memory, chronic fatigue, insomnia, depression and anxiety [58]. Carfì et al described that two months after discharge from the ICU, about 44% of COVID-19 patients showed a worsened quality of life, with more than 50% of them showing fatigue [60].…”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation